COMPONENTS OF DATA SCIENCE AND ITS APPLICATIONS (INTERNATIONAL JOURNAL OF SCIENTIFIC COMPUTING (IJSC), 2023)
Data Science is a multidisciplinary field that leverages statistical, mathematical, and computational techniques to extract insights from data. This article explores the components of data science, including data collection, cleaning, exploration, modelling, and visualization. It emphasizes the significance of machine learning, artificial intelligence, data governance, and ethics in driving the applications of data science across various sectors. By examining the role of data in today's world and its transformative potential, this article provides a comprehensive overview of the components of data science and its diverse applications in modern society.